Guayule rubber and latex content — seasonal variations over time in Argentina - Coates, W (2001)
Rubber from guayule (Parthenium argentatum Gray, Asteraceae) is essentially equivalent to that from the rubber tree (Hevea brasiliensis). Increased incidents of 'latex allergies', especially among health care workers, have resulted in a renewed interest in guayule, because it has been shown that individuals sensitive to latex allergies do not react to guayule latex. Little work documenting changes in guayule latex content with plant age, from season to season, or among lines has been reported. To provide some of this information and hence to assist with the commercialization of guayule, a project was initiated to determine rubber and latex changes over time in guayule plants growing in Catamarca, Argentina. Lines G7-14, N-565 and 11591 were sampled every 2 months, whereas lines AZ-5, AZ-3, P2-17, P1-12, P3-11, G10-130 and G1-16 were sampled every 6 months over a 3 year period. Statistically significant differences in plant weight, and in rubber and latex contents, were found among some lines. Plant weights were positively correlated with age. Latex and rubber contents showed little correlation with age. The latex and rubber contents were well correlated (0.73 for all lines). Latex and rubber production among some lines was statistically different. Seasonal effects on latex and rubber percentages were significant only for lines G7-14 and 11591, whereas seasonal effects on latex and rubber production were significant only for lines G7-14 and N-565. The results for the various lines indicates that time of harvest may not be critical to maximize yield. Harvesting the crop throughout the year would require a smaller capacity processing facility than seasonal harvesting and reduce the cost of a processing facility and production. © 2001 Elsevier Science B.V. All rights reserved.